2014
DOI: 10.4028/www.scientific.net/amm.513-517.4102
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization for PID Controller Parameters Based on Genetic Algorithm

Abstract: as an important research field of automatic control problems, PID parameter optimization's control effect depends on the proportional, integral and derivative values. Using trial and error testing to manually realize optimization PID parameters, the traditional ways are often time-consuming and difficult to meet the requirements of real-time control. In order to solve the problems and improve system performance, the paper proposes a PID parameter optimization strategy based on genetic algorithm. The paper esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…PID stands for proportional, integral, and derivative and is a classical controller used for several control applications (Metered et al 2015;Kesarkar and Selvaganesan 2015;Niu 2014;Gad et al 2017;Tammam et al 2013;Abdelrassoul et al 2016;Chen and Chang 2006). The PID controllers are so designed that continuous attention of the operator is eliminated.…”
Section: Control Theory-pid Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…PID stands for proportional, integral, and derivative and is a classical controller used for several control applications (Metered et al 2015;Kesarkar and Selvaganesan 2015;Niu 2014;Gad et al 2017;Tammam et al 2013;Abdelrassoul et al 2016;Chen and Chang 2006). The PID controllers are so designed that continuous attention of the operator is eliminated.…”
Section: Control Theory-pid Controlmentioning
confidence: 99%
“…The authors observed that the results were promising as compared to the conventional PID method. Niu (2014) had implemented GA-based optimization method to tune PID parameters of the active suspension system. Absolute error control is used as an objective function to tune the PID parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transfer function was then used to analyze the performance of the system and to design proper controllers to meet the design criteria. For the compensator design, the locations of the desired poles were found out from the proposed values of settling time, rise time and percentage overshoot [8,9]. Using root locus, it was found that a lead compensator is required to place poles in the desired locations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, precision agriculture variable rate fertilizer control strategy mainly around the PID control algorithm [8][9][10][11][12], fuzzy control rules [13][14] and the relevance vector machine [15] and other aspects of the research work commenced in improving the control system performance, increase precision fertilization made a lot of achievements and to promote the domestic development of intelligent variable fertilization seeder. Research process, due to the PID algorithm has the features of a simple structure, robustness and high reliability [16], has been widely used, however, PID parameter tuning is a complex optimization process that determines the performance of the control system, usually Engineering on tuning methods have decay curve method, Ziegler-Nichols step response method, ITSE optimal setting method, rapid titration and relay method and so on. This paper use of the analyzes of mechanism to establish the mathematical model of electro-hydraulic variable rate fertilization system, using Ziegler-Nichols method tuning PID controller parameters, and analysis parameters by testing the impact on system performance.…”
Section: Introductionmentioning
confidence: 99%